Pendampingan Pokdarwis Pembuatan Peta Wisata Di Kelurahan Kranggan Kota Mojokerto - Achmad Risdiyanto; Ilmia Putri Hariyono; Juan Dwi Saputra; Miftakhul Fitriyah; Miftakhul Mufidah; Nindy Pramudita; Riqlatus Sitta Wahyu (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Pokdarwis (tourism awareness group) is an institution founded by villagers whose members consist of local people who have concern and responsibility and act as a driving force to create a conducive environment and atmosphere for the development of tourism in the village area and to realize sapta charm (trustworthy, orderly, clean, cool, beautiful, friendly, memorable). One of them is the “SEJAHTERA” Pokdarwis which is located in Kranggan Village, Mojokerto City. Pokdarwis SEJAHTERA has a variety of excellent tours, for example "Sofia" batik, wooden crafts, salted egg entrepreneurs, accecories, car free days (which are usually held once a week) on Jalan Karimun Jawa (Gatoel housing) and various other excellent products .